Aplikasi Pemandu Wisata Religi Di Jawa Timur Berbasis Android - Abdul Basith; Muhyiddin Zainul Arifin; Moh Anshori Aris Widya (SAINTEKBU, 2021)
Religious tour is a new interested trend in this society. That point be evidenced with lots of religious activities. Starting from a tour guide, a tourist area manager, and prominent members of society in the village or in the city. The problems that be faced by religious traveller who want to travel in east java are lack of accurate information, details about tourism, and the tourist spot they're going to visit. To overcome those problems, researcher have designed and constructed a religious tour app in east java, supported by google maps and some details of such sightseeing details, short of travel descriptions, travel pictures as well as the direction directed by Google maps to guide to the tourist locations. This application is able to walk on the various platforms in mobile androids that will make it easier for tourism to do the search for location and religious tourist information in east Java.